Day 2 Wed, August 12, 2015 2015
DOI: 10.2118/174584-ms
|View full text |Cite
|
Sign up to set email alerts
|

Potential Evaluation of Ion Tuning Waterflooding for a Tight Oil Reservoir in Jiyuan OilField: Experiments and Reservoir Simulation Results

Abstract: Low salinity waterflood (LSF) is a promising improved oil recovery (IOR) technology. Although, it has been demonstrated that LSF is an efficient IOR method for many sandstone reservoirs, the potential of LSF in tight oil reservoir is not well-established. This paper presents a systematic evaluation of the potential of low salinity waterfloding for the tight reservoirs in Jiyuan Oilfield, China. This investigation pushes the application envelope of low salinity waterflooding towards the reservoir with low perme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…(5)), which in return impacts the double layer expansion, we examined the effect of concentration of monovalent cation (NaCl) and divalent cation (Mg 2+ , Ca 2+ ) on the disjoining pressure (Figs. [3][4][5]. Divalent cations however plays a more significant role in disjoining pressure than monovalent does at a certain concentration.…”
Section: Effect Of Ion Concentration On Disjoining Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…(5)), which in return impacts the double layer expansion, we examined the effect of concentration of monovalent cation (NaCl) and divalent cation (Mg 2+ , Ca 2+ ) on the disjoining pressure (Figs. [3][4][5]. Divalent cations however plays a more significant role in disjoining pressure than monovalent does at a certain concentration.…”
Section: Effect Of Ion Concentration On Disjoining Pressurementioning
confidence: 99%
“…One such technique that has gained interest within industry is low salinity water flooding (LSW), involving injection of low salinity brine into the reservoir under secondary and tertiary conditions [2]. It has been shown that salinity level and water chemistry, through its effect on Crude Oil/Brine/Rock (COBR), can exhibit significant incremental oil recovery from lab-scale to reservoir scale, in both sandstone and carbonated reservoirs [3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a pressing need to develop cost-effective techniques to enhance oil recovery in the period of low oil prices. Engineering the injected water chemistry and using water wisely to enhance oil recovery is a novel and emerging research area, which is called low salinity water flooding [4][5][6][7], smart water flooding [8][9][10][11][12], designer water flooding [13][14][15][16], or ion tuning water flooding [17,18]. Many researchers found that low salinity water injection could achieve an incredible additional oil recovery in sandstone and carbonate reservoirs from both experiments and field tests [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Changing water flood salinity/chemistry can increase oil recovery from sandstone and carbonate reservoirs by 5-25%, though why this happens is unclear [13,17,[19][20][21][22][23][24][25][26][27][28][29]. Several mechanisms have been proposed to describe how the low salinity effect (LSE) increases oil recovery, including: (1) fines mobilisation [30], (2) limited release of mixed-wet particles [30], (3) increased pH and reduced interfacial tension (IFT) similar to alkaline flooding [31], (4) multi-component ion exchange (MIE), (5) expansion of the double layer, (6) salt-in effect [12], and (7) osmotic pressure [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation